Can different conditioning activities and rest intervals affect the acute performance of taekwondo turning kick? - da Silva Santos, J. F.; Valenzuela, T. H.; Franchini, E. (The Journal of Strength and Conditioning Research, 2015)
This study compared the acute effect of strength, plyometric, and complex exercises (combined strength and plyometric exercise) in the countermovement jump (CMJ) and frequency speed of kick test (FSKT) and attempted to establish the best rest interval to maximize performance in the CMJ, number of kicks, and impact generated during FSKT. Eleven taekwondo athletes (mean ± SD; age: 20.3 ± 5.2 years; body mass: 71.8 ± 15.3 kg; height: 177 ± 7.2 cm) participated. One control and 9 experimental conditions were randomly applied. Each condition was composed of warm-up, conditioning activity (half-squat: 3 × 1 at 95% 1RM; jumps: 3 × 10 vertical jumps above 40-cm barrier; or complex exercise: half-squat 3 × 2 at 95% 1RM + 4 vertical jumps above 40-cm barrier), followed by different rest intervals (5-, 10-minute, and self-selected) before CMJ and FSKT. The conditions were compared using an analysis of variance with repeated measures, followed by Bonferroni's post hoc test. The alpha level was set at 5%. Significant difference was found in the number of kicks (F9,90 = 1.32; p = 0.239; and n^2 = 0.116 [small]). The complex method with a 10-minute rest interval (23 ± 5 repetitions) was superior (p = 0.026) to the control (19 ± 3 repetitions), maximum strength with a self-selected rest interval (328 ± 139 seconds; 18 ± 2 repetitions) (p = 0.015), and plyometric with a 5-minute rest interval (18 ± 3 repetitions) (p < 0.001). Our results indicate that taekwondo athletes increased the number of kicks in a specific test by using the complex method when 10-minute rest interval was used.